2020
DOI: 10.1186/s12885-019-6461-z
|View full text |Cite
|
Sign up to set email alerts
|

Does chemoradiotherapy benefit elderly patients with esophageal squamous cell cancer? A propensity-score matched analysis on multicenter data (3JECROG R-03A)

Abstract: Background: The aim of the present study was to assess the efficacy of concurrent chemoradiotherapy (CRT) or radiotherapy alone (RT-alone) in elderly patients with esophageal squamous cell carcinoma (ESCC). Methods: The clinical data of patients with ESCC treated with RT-alone or CRT were collected and retrospectively reviewed. The 1-, 3-and 5-year overall survival (OS) rates and the clinical characteristics correlated with survival were analyzed statistically. Propensity score matching (PSM) analyses were use… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
1
5
0
1
Order By: Relevance
“…Takeuchi reported a retrospective analysis showing significant inferior efficacy, even in selected patients ( 60 ). Chen also reported CRT may not improve the survival of elderly ESCC patients ( 61 ). Jingu suggested CRT should be carefully selected ( 62 ).…”
Section: Stage Ii/iii (Non-t4)mentioning
confidence: 99%
“…Takeuchi reported a retrospective analysis showing significant inferior efficacy, even in selected patients ( 60 ). Chen also reported CRT may not improve the survival of elderly ESCC patients ( 61 ). Jingu suggested CRT should be carefully selected ( 62 ).…”
Section: Stage Ii/iii (Non-t4)mentioning
confidence: 99%
“…compared patients ≥80 years with esophageal cancer treated with conventional dCRT with 2 younger patient cohorts (65–79 years and <65 years) treated with dCRT by propensity score matching and showed that the elderly cohort exhibited statistically significant evidence of an increased rate of severe radiation pneumonitis ( 12 ). Several studies have suggested that dCRT improves overall survival in elderly patients only in locally advanced stage compared with RT alone ( 13 , 14 ). Since elderly patients have unique issues, namely, life expectancy, comorbidities, and the risk of treatment-induced morbidity, chemoradiotherapy requires careful consideration and should be carefully selected in elderly EC patients ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…After PSM, 3,020 patients were included for further analysis, the 3- and 5-year OS and CSS in the CRT group were longer than those in the RT-alone group in five subgroup analyses stratified by age (ages 65–69; 70–74; 75–79; 80–84; ≥85, respectively). The 5-year survival rate of elderly cancer patients undergoing radical radiotherapy or radiochemotherapy is 9.7%~30.1% ( 18 , 19 ). Many previous clinical research results were consistent with our reports.…”
Section: Discussionmentioning
confidence: 99%